Clinical Pharmacology and nursing management (Philadelphia : J.B. Lippincott Company, 1993)
Introduction to pharmacology.--Therapy with drugs.--Administration of medications.--Special considerations in drug therapy.--Drugs that affect the nervous system.--Drugs affecting the cardiovascular system.--Drugs affecting the gastrointestinal system.--Drugs affecting the endocrine system.--Drugs affecting the inmune system.--Drugs affecting other body systems.--Drugs used for inflamations and infections.--Drugs affecting neoplastic diseases.--Nutritional supplements.-Miscellaneous drug families.
Incluye Apéndice.--Glosario.--Indice.
Keywords: Farmacología Clínica; Enfermería